The Relationship of Malnutrition and Skin Disease : A Comprehensive Systematic Review - Meli Tri Suciwulandari; Aditya Muhammad Gumay (The International Journal of Medical Science and Health Research, 2025)
Introduction: The skin's integrity is closely linked to nutritional status, with malnutrition—encompassing both under- and overnutrition—having the potential to precipitate or worsen a wide range of dermatological diseases. This systematic review aims to comprehensively evaluate and synthesize the existing literature on the relationship between malnutrition and various skin conditions, as well as the efficacy of nutritional interventions. Methods: Following the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 guidelines, a systematic search was conducted across five databases, including PubMed and Google Scholar. The review included primary research and systematic reviews published since 2015 that examined the link between measured nutritional status and specific skin diseases in human subjects. From an initial 298 records, 23 studies met the eligibility criteria and were included for data synthesis. Results: The synthesized evidence revealed a consistent and significant association between malnutrition and adverse skin outcomes. Meta-analyses showed that malnutrition substantially increases the risk of pressure injuries (Odds Ratio = 3.66) and surgical site infections (Odds Ratio = 1.81). Overnutrition was linked to a higher risk of atopic dermatitis (Hazard Ratio = 1.15), while specific deficiencies in vitamin D, protein, and zinc were associated with conditions like systemic sclerosis, vitiligo, and pruritus. All twelve studies evaluating nutritional interventions, such as specialized diets, supplementation, and protocol-based support, reported significant improvements in both skin health and nutritional status. Discussion: The findings confirm that nutritional status is a fundamental modulator of dermatological health, impacting inflammatory processes, immune function, and wound healing. The success of targeted nutritional support across various conditions underscores its value as a powerful therapeutic tool in dermatological care. Conclusion: This systematic review confirms that a strong and multifaceted relationship exists between nutritional status and skin health. The evidence synthesized from 23 studies demonstrates that malnutrition, whether characterized by undernutrition, overnutrition, or specific micronutrient deficiencies, consistently correlates with an increased risk and severity of a wide range of dermatological conditions. These include pressure injuries, impaired wound healing, inflammatory disorders like atopic dermatitis, and autoimmune diseases such as systemic sclerosis. The findings highlight that the impact of nutrition on the skin is profound, affecting its structural integrity, immune function, and regenerative capacity across diverse patient populations, from children to the elderly.